147k views
5 votes
Hey Guys !!!!

pls Help me out.....


Don't Spam!!​

Hey Guys !!!! pls Help me out..... Don't Spam!!​-example-1

2 Answers

1 vote

Answer:

D)
3m + 21

Explanation:

We know that the average is a value divided by 2: So we can calculate the average in terms of x:

We know that:


x = m + 9


y = 2m + 15


z = 3m + 18

To find the average of x, y, z we can add them then we can divide by 2 to find the average in terms of m:


m + 9 + 2m + 15 + 3m + 18 = 6m + 42

I have combined like terms and then using that I can divide this by 2:


6m + 42 / 2 = 3m + 21

User Austin Marusco
by
5.1k points
1 vote

Answer:

Hey There!

Let's solve...

First we need to find out the equation of x which is


x = (m + 9)/(2) \\

Now let's find out the equation of y which is


y = (2m + 15)/(2) \\

Now let's find out equation of z which is


z = (3m + 18)/(2) \\

On adding the three equations, we get


2x + 2y + 2z = m + 2m + 3m + 9 + 15 + 18

Now we get..


2(x + y + z) = 6m + 42 \\ \\ x + y + z = 3m + 21

Now let's find our the average of x,y snd z which is


(x + y + z)/(3) \\ which \: is \: \\ \\ (3m + 21)/(3)


now \: factor \: 3m + 21 \: which \\ is \: 3(m + 7)

Now simplify..


\frac{ \cancel{3}(m + 7)}{ \cancel{3}} \\

So answer is m+7

I hope it is helpful to you..

Cheers!____________

User Bert F
by
5.5k points